Maintenance dredging proceedings of a conference organised by the Institution of Civil Engineers and held in Bristol on 20-21 May, 1987. (Thomas Telford, 1987)
This title examines maintenance dredging and spoil disposal at UK ports. Other topics covered include field measurement and analysis, modelling and predicting channel sedimentations, the economics of port maintenance dredging by contract or direct labour and methods of payments.